PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN - Laia, Baziduhu (LPPM Universitas Nias Raya, 2024)
This research aims to determine the influence of service quality on consumer satisfaction at UD. Laia in Hilimondrege Raya Village. This type of research is quantitative research that is causal in nature. The sample in this research consisted of 100 consumers. The analytical method used in this research is simple linear regression analysis. The results of this research indicate that there is a significant influence between Service Quality and Consumer Satisfaction at UD. Laia in Hilimondrege Raya Village. In this research, a simple linear regression equation was obtained, namely: Y = 24.008 + 0.565 on consumer satisfaction. Then simultaneously there is a positive influence between the independent variable service quality (X) on the dependent variable consumer satisfaction (Y) using the SPSS 21.0 For Windows Evaluation Version program, obtaining an R Square value of 0.612 or 61.2%. The results of the hypothesis test (t test) obtained a t value of 5.128 > a t table value of 1.661 with a degree of freedom of 98 (100-2) at = 0.05 because 0.000 < 0.05, it can be concluded that service quality influences consumer satisfaction at UD . Laia in Hilimondrege Raya Village.